2017
DOI: 10.1038/eye.2017.46
|View full text |Cite
|
Sign up to set email alerts
|

Vessel diameter study: intravitreal vs posterior subtenon triamcinolone acetonide injection for diabetic macular edema

Abstract: PurposeTo detect and compare the vessel diameter effect of intravitreal vs subtenon injection of triamcinolone for diabetic macular edema (DME).MethodsSixty patients with DME who underwent triamcinolone injection either intravitreally (N=30) or under the tenon capsule (N=30) were included. Non-injected fellow eyes served as control. The main outcome measures were central retinal artery equivalent (CRAE), central retinal vein equivalent (CRVE), and artery-vein ratio (AVR).ResultsIn the intravitreal group, pre-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…28 Kurt et al stated that intravitreal and subtenon triamcinolone may lead to a significant constriction of retinal arteries and veins in DME. 29 According to a study evaluating the vascular changes in retinal vein occlusion, the deep retinal vessels become less telangiectatic after dexamethasone treatment. 30 Inflammation has been identified as a leading factor for vessel stiffness in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…28 Kurt et al stated that intravitreal and subtenon triamcinolone may lead to a significant constriction of retinal arteries and veins in DME. 29 According to a study evaluating the vascular changes in retinal vein occlusion, the deep retinal vessels become less telangiectatic after dexamethasone treatment. 30 Inflammation has been identified as a leading factor for vessel stiffness in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Kurt et al. recently reported similar anatomic and functional improvements after both IVTA and STTAI administrations in diabetic eyes [ 29 ]. Moreover, in this study, both routes of injection led to a significant constriction of retinal arteries and veins and, as a result, to the decline of vascular permeability and leakage [ 30 ].…”
Section: Discussionmentioning
confidence: 93%
“…TA is a corticosteroid that has antiangiogenic and anti-inflammatory effects that can inhibit VEGF and other cytokines, which enter the pathogenesis of macular edema due to RVOs and produce changes in the diameter and perfusions of the retinal vessel, improving BCVA and decreasing CMT [7,12,13] . Kurt et al [14] found some associations between vessel diameter, CMT, and IOP values after triamcinolone injection, suggesting that posterior subtenon TA injection causes retinal vessels constriction leading to a decrease in CMT and increase in the BCVA, which will be helpful in understanding the action mechanism of triamcinolone.…”
Section: Explanation Of the Main Finding Of The Studymentioning
confidence: 99%